Cognitive lingua-cultural methodology as a universal model for the formation of language - Zhanalyk Baltabayeva, Gaukhar Yersultanova, Kalbike Yessenova, Sayan Zhirenov, (Opción, 2019)
The purpose of the article is to prove that multilingual education is a universal matrix of dimensions, qualities, and approaches that encompass theories and practices of educational reform. On the basement of our cognitive linguacultural methodology, we presented four stages of language personality formation. Each stage fulfills its own specific functions and the set of certain skills are formed on each stage, which is equipped by the most effective methods and techniques. Experiment showed that the usage of cognitive lingua-cultural methodology promoted the effective formation of language personality who is able to be a participant of the publisitic discourse.